Analisis Jaringan Sosial Komentar Youtube Cuplikan “Louis Theroux: The Settler” - Maharani, Diva Nauli; Syahputra, A'riq Fatah; Khairunnisa, Risna; Bakry, Gema Nusantara (The Journal of Society and Media, 2026)
The documentary Louis Theroux: The Settlers (2025) generated significant public discourse following its release, particularly through a viral YouTube clip that gained over 800,000 views and 7,000 comments. This study examines the structure and dynamics of the comment section using Social Network Analysis (SNA) with a descriptive quantitative approach. The dataset consists of 7,448 comments from 5,402 users, forming 3,628 interaction networks. Data were collected via the YouTube API and analyzed using Gephi. Network-level findings show a diameter of 3, indicating efficient interaction paths, but a density of 0.0000, suggesting minimal interconnectedness. A high modularity score (0.814) reveals fragmented discussion clusters. At the actor level, @jessehash1583 was the most active commenter, while @edwardhomson6005 emerged as the most influential based on engagement metrics. Meanwhile, @Oml708t had the highest betweenness centrality, acting as a bridge between users. Overall, user participation was largely expressive and fragmented, with limited sustained dialogue. This study highlights patterns of digital communication and the role of key actors in shaping discourse on controversial socio-political issues